(untitled) (Texas Journal of Multidisciplinary Studies, 2021)
Traditionally, flour confectionery products, which include muffins, are in significant demand among almost all age groups of the population. The aim of the study was to develop a recipe and technology for preparing muffins using paste from white mulberry and sugar beet root crops. The experimental part of the work was carried out in the laboratories of the food technology department of the Bukhara Engineering Technological Institute.